Anti-Angiogenic/Anxiolytic Effect of Chlordiazepoxide: Evidence on Dual Activity for Cancer Patients - Reza Yarani; Kamran Mansouri; Azadeh Mahnam (International Journal of Hematology-Oncology and Stem Cell Research, 2011)
Angiogenesis which is the recruitment of new blood vessels is a critical Process in several chronic diseases and is an essential component of tumor or cancer progression. Development of therapies aimed at inhibiting the angiogenesis, in combination with classical anti-cancer therapies, is among the most intensively studied approaches to treat the cancer. In this study the effect of chlordiazepoxide (which is a proper anxiolytic drug) on angiogenesis in microcarrier-based collagen gel was assayed. Chlordiazepoxide beside its anxiolytic effect in patients showed strong inhibitory effect on human umbilical vein endothelial cells (HUVECs) tubulogenesis (angiogenesis) in collagen matrix, without toxic effects in the studied doses.